The challenges of growing great crystals – or at least good enough ones - Blake, Alexander J. (Acta crystallographica. Section C, Crystal structure communications, 2024)
The article of Sommer [Acta Cryst. (2024), C80, 337–342] provides a concise and effective introduction to the subject of growing crystals suitable for structure determination. The article of Sommer [Acta Cryst. (2024), C80, 337–342] provides a concise and effective introduction to the subject of growing crystals suitable for structure determination.